A cross-sectional study to evaluate ocular manifestations in end-stage renal disease patients attending tertiary care center - D. S. Kaushik; K. V. Ashwini; Srivatsa Angraje (The Pan-American Journal of Ophthalmology)
Context: Chronic renal failure leads to end-stage renal disease (ESRD), where patients rely on hemodialysis (HD). ESRD affects multiple organ systems, including the eyes, there is limited data on ocular complications among HD patients in India. Aims: The aim of the study was to analyze the clinical spectrum of ocular manifestations in ESRD patients on HD and investigate the relationship between the duration of dialysis and ocular complications. Settings and Design: A hospital-based cross-sectional study was conducted at a tertiary care center involving 75 ESRD patients. Methodology: Participants underwent comprehensive ophthalmic examinations, including tonometry and fundus examination. The study excluded patients with corneal dystrophy, renal transplant history, ocular trauma, or malignancy. Data on dialysis duration, frequency, and ESRD etiology were collected. Statistical Analysis Used: Nonparametric Mann–Whitney U test assessed the relationship between dialysis duration and ocular complications, with significance set at P < 0.05. Results: Among 150 eyes, 83.33% exhibited ocular abnormalities, with cataracts (50%) and conjunctival calcification (16%) being the most common findings. Significant correlations were found between dialysis duration and diabetic retinopathy (P = 0.01), hypertensive retinopathy (P = 0.005), and conjunctival calcification (P = 0.012). Conclusions: Ocular abnormalities are prevalent in ESRD patients undergoing HD, with dialysis duration significantly associated with specific conditions. Regular ophthalmologic evaluations are essential for managing ocular health in this population.